Antifungal agent utilization evaluation in hospitalized neutropenic cancer patients at a large teaching hospital - Vazin A (Drug, Healthcare and Patient Safety, 2015)
Afsaneh Vazin,1 Mohammad Ali Davarpanah,2 Setareh Ghalesoltani3 1Department of Clinical Pharmacy, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran; 2HIV Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 3International Branch of Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Iran Abstract: To evaluate pattern of using of three antifungal drugs: fluconazole, amphotericin B and voriconazole, at the hematology–oncology and bone marrow transplant wards of one large teaching hospital. In a prospective cross-sectional study, we evaluated the appropriateness of using antifungal drugs in patients, using Infectious Disease Society of America (IDSA) and National Comprehensive Cancer Network (NCCN) guidelines. All the data were recorded daily by a pharmacist in a form designed by a clinical pharmacist and infectious diseases specialist, for antifungals usage, administration, and monitoring. During the study, 116 patients were enrolled. Indications of prescribing amphotericin B, fluconazole, and voriconazole were appropriate according to guidelines in 83.4%, 80.6%, and 76.9% respectively. The duration of treatments were appropriate according to guidelines in 75%, 64.5%, and 71.1% respectively. The dose of voriconazole was appropriate according to guidelines in 46.2% of patients. None of the patients received salt loading before administration of amphotericin B. The most considerable problems with the mentioned antifungals were about the indications and duration of treatment. In addition, prehydration for amphotericin B and dosage of voriconazole were not completely compatible with the mentioned guidelines. A suitable combination of controlling the use of antifungals and educational programs could be essential for improving the general process of using antifungal drugs at our hospital. Keywords: utilization evaluation, fluconazole, amphotericin B, voriconazole, neutropenia